1999
DOI: 10.1073/pnas.96.26.15032
|View full text |Cite
|
Sign up to set email alerts
|

A subset of skin tumor modifier loci determines survival time of tumor-bearing mice

Abstract: Studies of mouse models of human cancer have established the existence of multiple tumor modifiers that influence parameters of cancer susceptibility such as tumor multiplicity, tumor size, or the probability of malignant progression. We have carried out an analysis of skin tumor susceptibility in interspecific Mus musculus͞ Mus spretus hybrid mice and have identified another seven loci showing either significant (six loci) or suggestive (one locus) linkage to tumor susceptibility or resistance. A specific sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…Our current data further suggest a tumor suppressive role of these cdk inhibitors in skin carcinogenesis. Consistent with the report of Nagase et al (1999), we observed a loss of expression of p21 and p27 when non-transgenic papillomas converted to malignant SCC ( Figure 5). At this stage, tumors begin to lose TGFbR and the signaling Smads (our unpublished data).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our current data further suggest a tumor suppressive role of these cdk inhibitors in skin carcinogenesis. Consistent with the report of Nagase et al (1999), we observed a loss of expression of p21 and p27 when non-transgenic papillomas converted to malignant SCC ( Figure 5). At this stage, tumors begin to lose TGFbR and the signaling Smads (our unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…All three of these cdk inhibitors are implicated by in vitro studies to be downstream targets of TGFb, and mediate TGFb-induced growth inhibition (Hannon and Beach, 1994;Datto et al, 1995;Polyak et al, 1994). Interestingly, Nagase et al (1999) have recently identi®ed two skin tumor resistant alleles Skts2 and Skts10 which lie near the loci of p21 and p27, respectively. Our current data further suggest a tumor suppressive role of these cdk inhibitors in skin carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a mouse strain carrying independent loci that inhibit different types of tumorigenesis is provided by M. spretus, which carries the Par1 locus on chromosome 11 to inhibit lung tumorigenesis 9 and independent loci on chromosomes 1, 4, 5, 7, 9, 12 and 16 to inhibit skin papilloma multiplicity. 18 The BALB/c strain also carries cancer resistance loci to two types of tumorigenesis, i.e., lung and liver. 19 We observed no significant correlation, however, between the lung and liver tumor phenotypes in a (BALB/cxC3H/He)F2 intercross (data not shown), indicating that BALB/c loci providing resistance to the two types of tumorigenesis are independent.…”
Section: Resultsmentioning
confidence: 99%
“…The Pthlh gene maps in the same chromosomal region as an M. spretus-derived skin cancer modifier locus (Skts12) that affects survival of tumor-bearing mice (Nagase et al, 1999). The present report, however, was not aimed to test Pthlh candidacy for Skts12, since we studied an inbred M. spretus strain (SPRET/Ei) different from the outbred M. spretus strain used to map the Skts12 locus (Nagase et al, 1999).…”
Section: Discussionmentioning
confidence: 99%